On Having a Body: Time and Divine Embodiment - Grillo, Jennie (Journal of Biblical literature, 2025)
This article sets recent understandings of the Hebrew Bible's presentation of divine embodiment within the broader discourse of the body in the humanities, and in particular the recent turn toward time within the long study of the body. Closer attention to time can problematize both halves of the statement "God has a body." The temporal discontinuities of God's body in its appearances to the ancestors across different sources in Genesis pose the question of whether "have" is really the right verb. And the question of whether "body" is really the right noun is addressed by examining differences between God's body and Job's body in the book of Job. In particular, the two factors of temporality and flesh emerge as definitional for what a body is, not only in Job but in Biblical Hebrew more generally; and the bodily appearance that the Hebrew Bible attributes to God does not fully share these factors with other bodies.